2014
DOI: 10.5999/aps.2014.41.5.505
|View full text |Cite
|
Sign up to set email alerts
|

Risk Acceptance and Expectations of Laryngeal Allotransplantation

Abstract: BackgroundLaryngeal allotransplantation (LA) is a technique involving transplantation of a deceased donor's larynx into a recipient, and it may be substituted for conventional laryngeal reconstruction. There are widely different views on LA, as the recipient is administered continuous, potentially life-threatening, immunosuppressive therapy for a functional or aesthetic result, which is not directly related to life extension. The purpose of this study was to analyze the difference in risk acceptance and expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The present study found results, which echo findings from other international studies and that from the allotransplantation conducted within South Korea [ 5 6 7 12 ]. Despite differences in transplantation type and study populations, the fact that study results were similar indicates that the most influential factor could be "expectations" of the general public group with the lack of knowledge regarding subject matter.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study found results, which echo findings from other international studies and that from the allotransplantation conducted within South Korea [ 5 6 7 12 ]. Despite differences in transplantation type and study populations, the fact that study results were similar indicates that the most influential factor could be "expectations" of the general public group with the lack of knowledge regarding subject matter.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have reported gaps in the knowledge regarding risk acceptance and expectations for composite tissue allotransplantation between experts and non-experts in a number of countries. In South Korea, similar studies have been conducted to evaluate risk acceptance and expectations for allotransplantation of the face, hands, feet, and larynx [ 5 6 7 ]. However, no such survey study has been performed on scalp allotransplantation within South Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Subjective information from the case reports of the two laryngeal transplant recipients reveal patient‐reported improvement in quality of life, although specific quality of life tools were not used. This has been borne out by previously published studies . The first patient went from being unemployed to working as a motivational speaker.…”
Section: Resultsmentioning
confidence: 89%
“…These considerations are exemplified in the literature to date, as evidenced by the 12 articles identified in our search that centered on public opinion and expert commentary on laryngeal transplantation ethics. [6][7][8][17][18][19][20][21][22][23][24][25] A survey of laryngectomy patients found a relatively strong feeling that laryngeal transplantation was an acceptable procedure. 20 Another study questioned the desirability of laryngeal transplantation when compared with double hand, heart, and lung transplantation in a group of laryngectomy patients, other solid organ transplant recipients, and healthy subjects, demonstrating that laryngectomees were willing to give up an average of 1.2 years of life for successful laryngeal transplantion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation